SIMULATION-BASED MEDICAL EDUCATION: the experience of Tashkent state medical university - Boymurodov, Sh.A.; Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Simulation-based education has become an integral part of modern medical training, offering a safe and controlled environment for developing clinical competencies. Advanced simulation technologies allow students to train for both emergency and routine clinical situations without risk to real patients, fostering confidence, motor coordination, and teamwork. This article provides an overview of the simulation-based education model and presents the experience of Tashkent State Medical University (TSMU) in developing one of the most advanced simulation centers in the region. The center, aligned with leading global standards including those of the University of Central Florida (USA), supports core disciplines such as surgery, internal medicine, pediatrics, and intensive care. The article highlights the structure, equipment, training modules, and the broader educational and patient safety implications of simulation-based learning. This is a continuation of our publications in this direction [1-18]. The authors hope that this message will further explain the possibilities of the modern educational process in medicine. Keywords: medical education, simulation education, Tashkent State Medical University